Communication Strategy of Pondok Pesantren Putri Walisongo in Building Santri Creativity Through Musabaqah Hifdzil Qur'an - Khoiriyatul Ummah; Ahmad Fakhrudin Fajrul Islam (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study examines the communication strategies employed by Pondok Pesantren Putri Walisongo Cukir Jombang to foster santri creativity through Musabaqah Hifdzil Qur’an (MHQ). While previous studies have focused on tahfidz coaching and tilawah performance, the role of structured communication in developing creative capacities remains underexplored. This research employs a qualitative descriptive approach, collecting data through semi-structured interviews, participatory observation, and documentation with the kyai, MHQ coach, administrators, and five active students. Data were analyzed using Miles and Huberman's interactive model, validated through source, technique, and time triangulation. Findings reveal a multi-layered communication strategy including collaborative planning, intensive interpersonal mentoring, sustained training cycles, Islamic value-based motivation, flexible individualized coaching, and institutional coordination with formal schools. These practices cultivate disciplined Qur’anic creativity, reflected in memorization management, Qur’anic recitation exploration, individual talent development, mental resilience, and a supportive learning environment. This study contributes to Islamic communication scholarship by conceptualizing MHQ coaching as a value-based communicative ecosystem. Its implications extend to similar religious education contexts globally, including tahfidz programs in Southeast Asia and the Middle East.